Donald B. MacMillan (1874-1970) - MacMillan, Miriam (ARCTIC, 1984)
. MacMillan joined Peary's polar expedition in 1908. His life was centered on the Arctic for the next 46 years, most of which he spent aboard the Bowdoin. In fact, Mac's last trip North aboard the Bowdoin came in 1954, when he was 80 years old. Between 1913 and 1917, while in North Greenland, Mac drew on his experience and observation to conceive the design for the 88-foot Bowdoin, a wooden schooner of incredible strength that took its name from Mac's alma mater. . During 26 voyages between 1921 and 1954, MacMillan sailed her to and explored parts of North Greenland, Ellesmere Island, Bay Fjord, Eureka Sound, Labrador, Baffin Island, Iceland, and the east and west coasts of Greenland. Over the years, he mapped many previously uncharted northern waters. Owing to his unique and extensive knowledge of those areas, MacMillan was recalled to active duty by the U.S. Navy in her "home" waters. The contributions made by MacMillan and his crews to the knowledge and understanding of the North are too numerous to elaborate here. They include studies in the botany, ornithology, meteorology, oceanography, archaeology, glaciology, and anthropology of the regions explored. As well, Mac and his crews demonstrated that airplanes could be used effectively above the Arctic Circle and that short-wave radio could provide instant communication with the rest of the world. Those scientific and technical accomplishments - "firsts" in their time - were paralleled by Mac's interest in and love for the native people with whom he often lived, whose languages he mastered, and by whom he was deeply revered. .